2012
DOI: 10.1101/gad.179895.111
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction of ligand–receptor pairs specifying stomatal patterning

Abstract: Valves on the plant epidermis called stomata develop according to positional cues, which likely involve putative ligands (EPIDERMAL PATTERNING FACTORS [EPFs]) and putative receptors (ERECTA family receptor kinases and TOO MANY MOUTHS [TMM]) in Arabidopsis. Here we report the direct, robust, and saturable binding of bioactive EPF peptides to the ERECTA family. In contrast, TMM exhibits negligible binding to EPF1 but binding to EPF2. The ERECTA family forms receptor homomers in vivo. On the other hand, TMM assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
419
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(438 citation statements)
references
References 34 publications
18
419
0
1
Order By: Relevance
“…Mutations in TMM induce pattern violations in the form of excess stomata in direct contact 4,5 . Along with TMM, ERECTA-family LRR receptor-like kinases perceive secreted peptide ligands 6,7 . For example, the epidermal patterning factor (EPF)2 and EPF1 ligands, which are members of the EPF/EPF-like family, are specifically and respectively expressed in early-and late-stage stomatal precursor cells.…”
mentioning
confidence: 99%
“…Mutations in TMM induce pattern violations in the form of excess stomata in direct contact 4,5 . Along with TMM, ERECTA-family LRR receptor-like kinases perceive secreted peptide ligands 6,7 . For example, the epidermal patterning factor (EPF)2 and EPF1 ligands, which are members of the EPF/EPF-like family, are specifically and respectively expressed in early-and late-stage stomatal precursor cells.…”
mentioning
confidence: 99%
“…ERECTA-family receptors bind to both EPF1 and EPF2 in vitro, but they exhibit specificity in vivo during stomatal development: EPF2-ERECTA pair for initiation and EPF1-ERL1 pair for spacing division steps (Lee et al 2012). Although different expression patterns of these EPFs and their corresponding main receptors during stomatal development may contribute to in vivo specificity in part, it is possible that each EPF signal recruits specific signaling components in vivo to form multireceptor protein complexes to regulate different developmental processes.…”
Section: Factors That Determine the Specificity Of Cle And Epf Signalmentioning
confidence: 99%
“…It has been known that ERECTA and its two functional paralogs ERL1 and ERL2 have a role in controlling stomatal patterning and differentiation by perceiving the signals from some EPF peptides, such as EPF1 and EPF2. Biochemical and phenotypic studies using mature EPF1 and EPF2 peptides further established EPF2-ERECTA and EPF1-ERL1 as ligand -receptor pairs specifying two steps of stomatal development: initiation and spacing division (Lee et al 2012). Two other EPF-like peptides, EPFL4 and EPFL6, have redundant functions as ERECTA signals in a different developmental process: inflorescence growth (Uchida et al 2012a).…”
Section: Erecta Involved In Various Epf Peptide Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Likewise, TMM, forming a receptor complex with ERECTA family members, was found to regulate the proper stomatal distribution and differentiation. 23 Recently, SUPPRESSOR OF BIR1-1 (SOBIR1) was found to associate specifically with various RLPs that either function in plant development or in plant immunity. It has been demonstrated that SOBIR1 physically interacted with Cf-4, Ve1, LepR3, Rlm2, AtRLP1, AtRLP23, AtRLP30 and AtRLP42, and was required for the proper function of these RLPs.…”
Section: Introductionmentioning
confidence: 99%